2018
DOI: 10.1016/j.brainres.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

CSF Aβ1–42, but not p-Tau181, differentiates aMCI from SCI

Abstract: CSF Aβ, but not p-Tau level was significantly associated with aMCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Moreover, we verified that 45.16% of aMCI individuals who completed the follow-up progressed to ADD after 5 years, corresponding to an annual conversion rate of approximately 9%, which is in agreement with previous studies [25,26]. Prediction of ADD in a short period of time appears much more relevant in a clinical perspective than prediction of dementia in a 6 17 †ADD Alzheimer's disease dementia, aMCI amnestic mild cognitive impairment, AUC area under the curve, ROC receiver operating characteristic. ‡Youden index was used more distant future.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, we verified that 45.16% of aMCI individuals who completed the follow-up progressed to ADD after 5 years, corresponding to an annual conversion rate of approximately 9%, which is in agreement with previous studies [25,26]. Prediction of ADD in a short period of time appears much more relevant in a clinical perspective than prediction of dementia in a 6 17 †ADD Alzheimer's disease dementia, aMCI amnestic mild cognitive impairment, AUC area under the curve, ROC receiver operating characteristic. ‡Youden index was used more distant future.…”
Section: Discussionsupporting
confidence: 91%
“…This cohort underwent lumbar puncture followed by CSF biomarkers evaluation and was enrolled in the study until 2018. The baseline cross-sectional and the 3year follow-up studies have already been previously published [5,6]. In brief, patients were enrolled in a systematic way with clinical evaluations by a behavioral/geriatric neurologist and a neuropsychological specialist in order to detect progression to ADD in the aMCI group.…”
Section: Subjectsmentioning
confidence: 99%
“…When compared to MCI, the SCD individuals showed significantly lower levels of t-tau and p-tau, whereas differences in the Aβ42 levels were less pronounced [91]. Furthermore, a recent study reported significantly lower levels of Aβ42 in SCD than the controls, despite similar levels of t-tau and p-tau [92]. In a recent paper, 46% of SCD displayed brain amyloidosis, whereas 18% of them showed preclinical AD (A+T+) at CSF profile [93].…”
Section: Pre-mci: Neuropsychological and Biomarkers Findingsmentioning
confidence: 99%
“…The total number of participants recruited in all the studies was 7,035 (mean 234.5±274.23), with a mean age of 52.87 years (SD±7.79) and female predominance (4,355 individuals; 61.9%). Only one study analyzed biomarkers in individuals with SCD 13 , while another study analyzed SCD and individuals who converted from nondemented to dementia 14 .…”
Section: Resultsmentioning
confidence: 99%